Impending Mental Health Issues During Coronavirus Disease 2019 – Time for Personalized Nutrition Based on the Gut Microbiota to Tide Over the Crisis? - Dhar, Debojyoti (Frontiers in Neuroscience, 2022)
Covid-19 is a major pandemic facing the world today caused by SARS-CoV-2 which has implications on our mental health as well. The uncertain future, fear of job loss, lockdown and negative news all around have taken a heavy toll on the mental health of individuals from across the world. Stress and anxiety can affect the Covid-19 patients even more. Recent study suggests Covid-19 infection may lead to post-traumatic disorder (PTSD). Certain prebiotics and probiotics have been shown to have anxiolytic effect through gut microbiota modulation. Incidentally, preliminary report also suggests a differential microbial profile in Covid-19 patients as compared to healthy individuals. Gut microbiota’s role in anxiety and depression is well studied. The importance of the “gut-brain” axis has been implicated in overall mental health. It is known that diet, environmental factors and genetics play an important role in shaping gut microbiota. Trials may be initiated to study if personalized diet and supplementation based on individual’s gut microbiome profile may improve the general mental wellbeing of people prone to anxiety during this pandemic. Also, Covid-19 patients may be provided personalized nutritional therapy based on their gut microbiota profile to see if PTSD and anxiety symptoms can be alleviated.